Biolipídio B2: desenvolvimento de um veículo estável para reposição hormonal transdérmica nanoestruturada - Queiroz, Dinalva Brito de (2013)
The hormone administration by the oral route is frequently related with different many side effects. The aim of this study was to evaluate the safety and efficacy of a new product intended to transdermal hormone replacement nanostructured (TRHN) therapy, based on a patented under No. US 2013/0123220A1 formulation. This formulation was able to restore serum levels of estradiol (0.1%) + estradiol (0.25%) in 122 postmenopausal women with a mean age of 56.88 (± 6.27). The assessment is part of a longitudinal prospective study. Clinical parameters, including the degree of satisfaction with symptom relief, serum concentrations of estradiol, weight, blood pressure, were compared between the beginning and the end of treatment. The findings show that BIOLIPÍDEO B2® was safe and effective in restoring hormonal serum levels without side effects. The satisfaction with treatment was 92%. Serum concentrations of estradiol was significantly higher after treatment (p <0.05). Weight and systolic and diastolic blood pressure showed no significant differences (p> 0.05) during treatment. No vaginal bleeding was observed. Evaluation of bilateral breast mammography treatment found normal results in all women. This study shows for the first time the effectiveness of a transdermal formulation nanostructured in the transdermal delivery of estradiol and estriol measured in vivo using Confocal Raman Spectroscopy. The formulation of BIOLIPÍDEO/B2® is safe and effective in restoring serum estradiol levels and alleviates menopausal symptoms. The formulation can serve as a good choice for hormone replacement therapy to protect against post-menopausal symptoms.